Synthesis of an antiaromatic circulenophane - Pazhouhan Fekri, Afra (2020)
Otherwise unstable antiaromatic compounds can be studied when they are integrated into a bigger π-conjugated system. Cyclooctatetraene (COT) compounds are easy to synthesize and study, but they reside in a non-planar saddle-shaped conformation. Planarized COT, however, is an 8π 8-membered antiaromatic structure. A hetero[8]circulene is one option to overcome the non-planar conformation barrier. The surrounding aromatic π-system in a hetero[8]circulene core assists in creating a smaller bond angle, thus resulting in a planar diazadioxa[8]circulene. This thesis addresses a synthetic pathway towards having a suitable compound for studying the concept of antiaromaticity in planarized cyclooctatetraenes (COTs). For further research, there are two means of evaluating aromaticity. According to the Nucleus-Independent Chemical Shift (NICS) values obtained by computational chemistry, magnetic current of the COT core can be investigated. Furthermore, the synthesized compound can be analysed using NMR spectroscopy. Antiaromaticity of the hetero[8]circulene can be proven by locating a proton near the COT core so that the chemical shift of the proton changes due to the proximity to the ring current. To apply this theory, cyclophane-chemistry has been used to create a system in which a circulene substrate bearing a bridge-type linker containing protons is located in its centre. The linker is covalently bonded through the pyrrole nitrogen atoms of the circulene system. Creating this system enables us to study further the antiaromaticity of the circulenophane compound synthesized in this project.